Strategies to control myopia in children: a review of the findings from the Anyang Childhood Eye Study - Li, Shi-Ming; Wang, Ningli; Childhood Eye Study Group, the Anyang (Annals of Eye Science, 2018)
Myopia in children remains a major public health problem worldwide, especially in some Asian countries such as China, Singapore and Japan. Although many interventions have been attempted, few has been proven to be effective in controlling onset and progression of myopia in children. Environmental factors, genetic susceptibility or ethnic differences can affect the efficacy of these interventions. However, many questions remain unclear and even controversial for controlling myopia. China has the biggest population with myopia, especially for children myopia. Thus, it is of importance to present what achievements Chinese scientists have made in the field of myopia control in children. We summarize the current findings on myopia control in children from the Anyang Childhood Eye Study, including epidemiological data, clinical trials, systematic reviews and meta-analyses, and compare them with studies in other countries to find potential clues for controlling myopia in children.